Integrating Machine Learning for Dynamic Resource Allocation in Civil Engineering Project Scheduling - Thandiwe Mokoena; Sipho Nkosi (Universitas Sains dan Teknologi Komputer, 2025)
Civil construction projects globally are growing more complex because of resource constraints, environmental constraints and schedule uncertainties accumulate. The task presented here generates a machine framework based on learning to address these issues by enabling dynamic, interpretable, and sustainable planning the allocation of resources for comprehensive infrastructure scheduling. The method combines gradient enhanced decision trees and time-based convolutional networks driven by immediate sensing and digital replicas technologies for capturing nonlinearity and time-dependent relationships, thereby maintaining the sensitivity of the predictions to altered situational parameters. Rigorous assessments carried out on urban infrastructure across multiple locations. Projects demonstrate that the proposed model enhances planning precision by more than twenty percent and significantly improves average resource usage when compared to conventional optimization techniques. In addition to measurable efficiency benefits, the structure offers human impact via reduced materials waste reduction and energy efficiency enhancement, promoting global sustainability initiatives while guaranteeing safer construction advancement The strategy's reasoning equips project leaders to interpret and apply every recommendation instantly, promoting the development of managerial trust and fostering integration through daily routines. This combination of predictive capability, transparency, and environmental sustainability offers Civil engineering managers equipped with a robust tool to complete projects ahead of schedule and ensure enduring stability. The following sections outline the integrated method, present empirical data, and respond to the broadened strategies, methodologies, and investigatory pathways for upcoming sustainable infrastructure growth.